Comparative analysis of clinical characteristics of symptomatic pituitary adenomas in elderly patients: a consecutive series of 114 patients - Wang, Run; Han, Xiaodi; Xie, Cheng; Zhang, Qinghua; Kan, Liang; Han, Sheng (Frontiers in Endocrinology, 2024)
Background: Pituitary adenomas (PAs) present with clinical features such as neuroendocrine abnormalities and mass effects, common in the general morbidity population. However, in elderly patients, the disease progression renders some clinical features difficult to detect and identify in time. Consequently, elderly patients with PAs are often not identified and receive sufficient intervention on time to achieve a satisfactory outcome. Methods: Clinical data were collected from 114 consecutive patients older than 70 years with PAs who had undergone surgery. Based on the average age, the patients were categorized into a younger group and an elder group, and were statistically analyzed and compared. Results: Sixty-five males (57.0%) and 49 females (43.0%) were included in the study, with an average age of 73.2 years. Their common preoperative symptoms included vision impairment, followed by headache and vomiting, and visual field defect. The milder the preoperative visual impairment, the greater the possibility of post-operative visual improvement (P=0.001). The tumors were primarily non-functional pituitary adenomas (NFPAs, 73.7%), with a high degree of suprasellar invasion but a low degree of parasellar invasion (P<0.0001). For further analysis, based on the average age, we categorized the patients into younger (age< 73 years, 59 cases) and elder (age≥ 73 years, 55 cases) groups. The elder group was more likely to have preoperative vision impairment problems (P=0.044), whilst post-operative visual improvement was worse (P=0.001). The elder group also had a more severe suprasellar invasion (P=0.009), with a higher proportion of NFPA than the younger group (P=0.006). Compared to the younger group, the tumors in the elder group were larger (P=0.039), and had a higher rate of apoplexy (P=0.039), and were more likely to have comorbid postoperative complications (P=0.031), such as fever and cerebrospinal fluid (CSF) leakage, compared to the younger group. Conclusions: Elderly patients with PA had specific clinical characteristics. Their relatively worse pre- and post-operative conditions and intraoperative findings illustrated the need for early surgery.